Lexical Borrowing Used by Food and Beverage Product of One Selected Resto in Pekanbaru - Satria Abdurahman; Maspufah Maspufah; Yeni Afriyeni (LPPM STBA Persada Bunda, 2023)
Sultan Resto features a particularly Malay character by incorporating architectural embellishments from the Siak Sultanate, which is now popular in Pekanbaru, and serves real Malay home food. The purpose of this research was to find out kind and change of meaning in process of borrowing words that were happened in Food & Beverage Product of Sultan resto. The researcher used some theories about borrowing words to support the research from Baugh, Noam chomsky, and Martin Haspelmath. The researcher used descriptive qualitative method to analyze and describe the data. The researcher used recording for taking the video in Food & Beverage Product of sultan resto as the unit of analysis. To support the analysis, the researcher used cooking dictionary and some english dictionaries. As the result, the researcher found 20 words of borrowing words. The words were divided into three kinds of borrowing words and it was found that there were sixth loan words, ninth loan blend, and fifth loan shift. Then there were two kinds of changes of meaning, it consists of nineth Narrowing of meanings and two Extension of meanings. it could be concluded that the borrowing words from English and France languages especially in Sultan resto’s Food & Beverage Product were quite high.